2022
DOI: 10.7717/peerj.13215
|View full text |Cite
|
Sign up to set email alerts
|

Nickel mine soil is a potential source for soybean plant growth promoting and heavy metal tolerant rhizobia

Abstract: Mine soil is not only barren but also contaminated by some heavy metals. It is unclear whether some rhizobia survived under extreme conditions in the nickel mine soil. Therefore, this study tries to isolate some effective soybean plant growth promoting and heavy metal resistant rhizobia from nickel mine soil, and to analyze their diversity. Soybean plants were used to trap rhizobia from the nickel mine soil. A total of 21 isolates were preliminarily identified as rhizobia, which were clustered into eight group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Some representatives of Rhizobium were resistant to high concentrations of heavy metals. They also had good nitrogen-fixing capacity and thus improved plant growth, allowing them to be used as biofertilizers [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Some representatives of Rhizobium were resistant to high concentrations of heavy metals. They also had good nitrogen-fixing capacity and thus improved plant growth, allowing them to be used as biofertilizers [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heavy metals are important inorganic pollutants in recent years, such as Cu, Ni, Cd, Zn, Cr, and Pb. The studies of symbiosis with these heavy metals are more limited than light metals, mainly focused on Rhizobium and Ensifer species [60][61][62][63][64][65][66][67]. Some studies indicate that the combination of Rhizobium and arbuscular mycorrhizal fungi (AM) induces plant tolerance under As stress [63].…”
Section: Symbiosis Under Abiotic Stress and Its Challengesmentioning
confidence: 99%
“…Some studies indicate that the combination of Rhizobium and arbuscular mycorrhizal fungi (AM) induces plant tolerance under As stress [63]. Others showed that in Ni, Cu, Cr, Cd, and Zn, the symbiont tolerance varies according to the metal type, but the strain alleviates the effect of heavy metals in soybean [64]. Some Rhizobium species can nodulate species of Phaseolus, Trifolium, and Vicia under normal conditions but also can improve the seed germination, biomass, and chlorophyll content in these species under Cd-stress, and their response level depend more on the genotype of the plant associated with these rhizobia.…”
Section: Symbiosis Under Abiotic Stress and Its Challengesmentioning
confidence: 99%
“…[ 17 ] Rhizobium symbiosis has also been reported to improve the tolerance of alfalfa and soybean to cadmium, lead, zinc, and copper. [ 18 ] However, its role in V uptake and accumulation in legumes is still unclear. In the absence or limitation of molybdenum (Mo), the use of V instead of Mo on the active site of nitrogenase may play a more prominent role in nitrogen fixation.…”
Section: Introductionmentioning
confidence: 99%